Biotin for the treatment of nail disease: what is the evidence?. (19th May 2018) - Lipner, Shari R.; Scher, Richard K.
Abstract: Aim: To describe the pharmacology, mechanism of action, and clinical reports using biotin to treat nail conditions. Methods: A review of articles indexed for MEDLINE on PubMed using keywords 'biotin' and 'nail' was performed and applicable articles were selected for review. Results: Clinical trials have shown an improvement in firmness, hardness, and thickness of brittle nails with oral biotin. There are some case reports and series demonstrating that oral biotin may improve triangular worn down nails, trachyonychia, and habit tic nail deformity. Conclusions: Oral biotin has been used to treat several nail conditions with promising results. Further larger clinical trials with controls are necessary to determine efficacy and optimal dosing.